Disparities in prevalence and barriers to hypertension control: a systematic review - Elnaem, Mohamed Hassan Abdelaziz; Mosaad, Manar; Abdelaziz, Doaa H.; Mansour, Noha O.; Usman, Abubakar; Elrggal, Mahmoud E.; Cheema, Ejaz (MDPI, 2022)
Controlling hypertension (HTN) remains a challenge, as it is affected by various factors in different settings. This study aimed to describe the disparities in the prevalence and barriers to hypertension control across countries of various income categories. Three scholarly databases—ScienceDirect, PubMed, and Google Scholar—were systematically examined using predefined search terms to identify potentially relevant studies. Original research articles published in English between 2011 and 2022 that reported the prevalence and barriers to HTN control were included. A total of 33 studies were included in this systematic review. Twenty-three studies were conducted in low and middle-income countries (LMIC), and ten studies were from high-income countries (HIC). The prevalence of hypertension control in the LMIC and HIC studies ranged from (3.8% to 50.4%) to (36.3% to 69.6%), respectively. Concerning barriers to hypertension control, patient-related barriers were the most frequently reported (n = 20), followed by medication adherence barriers (n = 10), lifestyle-related barriers (n = 8), barriers related to the affordability and accessibility of care (n = 8), awareness-related barriers (n = 7), and, finally, barriers related to prescribed pharmacotherapy (n = 6). A combination of more than one category of barriers was frequently encountered, with 59 barriers reported overall across the 33 studies. This work reported disparities in hypertension control and barriers across studies conducted in LMIC and HIC. Recognizing the multifactorial nature of the barriers to hypertension control, particularly in LMIC, is crucial in designing and implementing customized interventions.